CROWDFUNDING WAQF MODEL: PERLINDUNGAN HUKUM DANA WAKAF YANG DIKUMPULKAN MELALUI PLATFORM CROWDFUNDING - Fadhila Shaffa Luthfie; Helza Nova Lita; Nun Harrieti (Legal Standing : Jurnal Ilmu Hukum, 2022)
Nowadays, there is an innovation of collecting waqf fund through crowdfunding that will help nazhir’s responsibility in managing and developing waqf assets. This method well-known as Crowdfunding Waqf Model that classified into donation-based crowdfunding. In accordance with unissued regulation regarding donation-based crowdfunding, collecting waqf fund through crowdfunding is an urgent topic to be discussed concerning how is the legal protection of waqf assets in the form of collecting waqf fund through crowdfunding. This research uses normative juridical approach, namely outlining existing problems and discuss according to applicable regulations. The steps of this research encompass steps, i.e: library research of using secondary data and field research in the form of interview. This research concludes that the legal protection in collecting waqf fund through crowdfunding inadequate and still relies on transparency and integration with related regulations. It is necessary to reform waqf regulation in Indonesia that encompass technology development, and creating regulation on donation-based crowdfunding specifically in order to creating legal certainty for the collecting waqf fund activity through technology.